Sexual dimorphism of gut microbiota at different pubertal status - Xin Yuan; Ruimin Chen; Ying Zhang; Xiangquan Lin; Xiaohong Yang (Microbial Cell Factories, 2020)
Abstract Background Accumulating evidence infer that gut microbiome-host relations are key mediators or modulators driving the observed sexual dimorphism in some disease onset and progression. To date, the sex-differences of gut microbiota at different pubertal status have not been reported. Objective To determine the characteristics of gut microbiota of both genders at different pubertal status. Methods Gut microbiota was analyzed in 89 Chinese participants aged 5–15 years. Participants were divided into pre-puberty and puberty groups for both male and female. The composition of gut microbiota was investigated by 16S rRNA-based metagenomics. Ecological representations of microbial communities were computed. The prediction of metagenomic functional content from 16S rRNA gene surveys was conducted. Results There were 49 males (9.76 ± 2.15 years) and 40 females (9.74 ± 1.63 years); 21 males and 26 females were at puberty. At genus level, Alistipes, Megamonas, Oscillospira and Parabacteroides were more prevalent in girls than in boys (p < 0.05). There were no significantly differences of alpha-diversity between genders, which was independent of pubertal status. The beta-diversity was significantly different in pubertal subjects between genders. Using statistical analyses, we assigned genera Dorea, Megamonas, Bilophila, Parabacteroides and Phascolarctobacterium as microbial markers for pubertal subjects. The predicted metabolic profiles differ in both pubertal and pre-pubertal groups between genders. Conclusion This cross-sectional study revealed that sex differences in the gut microbiota composition and predicted metabolic profiles exist before puberty, which become more significant at puberty. The identification of novel puberty bacterial markers may disclose a potential effects of gender-related microbiota profiles on puberty onset.